Letting It Flow: A Phenomenology of Water in the Age of Modern Technology - Barbaza, Remmon E. (Archīum Ateneo, 2024)
This essay seeks to initiate a phenomenology of water in the age of modern technology within a Heideggerian framework. Insofar as it holds sway as the essence of modern technology, Ge-stell (enframing) blocks the appearance of water as water. Instead, like most other “natural resources,” water appears as the resource that is extracted, manipulated, and made readily available for universal distribution and instant consumption, but detached from its origin in earth and sky. A disruption in the handiness of water, however, such as is occasioned by water shortage or massive flooding, offers the possibility of inviting human beings to recover their primordial relationship with water, as that on which their life depends and one that they cannot partake of in a sustainable way without a truthful and simple awareness of its origin.